Mapping the future of high value manufacturing in India - Rajat Kathuria; Mansi Kedia; Uttara Balakrishnan (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Indi's stagnating manufacturing sector has become a serious cause of concern for Indian policy makers. Several reasons have been identified for this slowdown, including lack of policy focus, unsupportive external environment, etc. Given the importance of the manufacturing sector and its potential to contribute to growth and employment, corrective measures must be implemented almost immediately to salvage the sector. In this context, the paper analyzes the potential for India to develop its high value manufacturing sector and provides recommendations on measures to achieve this objective. In the absence of extensive literature in this area, the paper begins by conceptualizing a definition of high value manufacturing using two different approaches. Secondary data analysis tells us that high value manufacturing in India exists only in islands. Cross country comparisons with other East Asian economies such as Korea, Japan and China reveal that India has an opportunity to develop a comparative advantage in other sectors including electronics and computer hardware. Using Hausmann's product space analysis, the opportunity set for India is identified. Consequently, using the "density" measure sectors and industries have been ranked on the basis of ease in achieving comparative advantage. The policy recommendations based on the secondary data analysis and case study interviews help us arrive at recommendations on mapping the future of high value manufacturing in India.
Keywords: L60; N65; O3; O14; 330; High Value Manufacturing; Product Space; India; East Asia; Industrial Policy; High Skill; Research and Development; Manufacturing